Compositionality and refinement in model-driven engineering - Davies, J; Gibbons, J; Milward, D; Welch, J (2012)
Model-driven engineering involves the automatic generation of software artifacts from models of structure and functionality. The use of models as 'source code' has implications for the notions of composition and refinement employed in the modelling language. This paper explores those implications in the context of object-oriented design: establishing a necessary and sufficient condition for a collection of classes to be treated as a component, identifying an appropriate notion of refinement for the generation process, and investigating the applicability of data and process refinement to object models. © 2012 Springer-Verlag.